Undifferentiated and Dedifferentiated Endometrial Carcinomas With POLE Exonuclease Domain Mutations Have a Favorable Prognosis. (August 2017) - Espinosa, Iñigo; Lee, Cheng-Han; D'Angelo, Emanuela; Palacios, José; Prat, Jaime
Abstract : POLE exonuclease domain mutations have recently been described in undifferentiated endometrial carcinoma but, because of the rarity of this aggressive type of endometrial cancer, their prognostic significance is unknown. We have analyzed the immunophenotype (ARID1A, MLH1, PMS2, MSH2, MSH6, p53, β-catenin, and SMARCB1) and mutational status ( POLE, PIK3CA, and PTEN ) of 21 undifferentiated carcinomas (8 undifferentiated and 13 dedifferentiated carcinomas). Loss of ARID1A expression was observed in 9 of 19 cases (47%), loss of expression of at least 1 DNA mismatch repair protein in 7 (7/21; 33%), and p53 immunoreaction was aberrant (mutated/inactivated) in 11 cases (11/21; 52%). All tumors were negative for β-catenin. Normal nuclear SMARCB1 (INI1) staining was found in all but 1 dedifferentiated case. Two undifferentiated and 7 dedifferentiated carcinomas showed POLE exonuclease domain mutations (9/21; 42%). PIK3CA mutations occurred in six tumors (6/21; 28%) (2 undifferentiated and 4 dedifferentiated carcinomas). PTEN mutations were found in 7 of 15 cases (47%) (4 undifferentiated and 3 dedifferentiated carcinomas). POLE -mutated undifferentiated and dedifferentiated endometrial carcinomas were more frequently stage I tumors than similar carcinomas lacking exonuclease domain mutations (7/9; 78% vs. 3/12; 25%; P =0.023) and patients had significantly better outcome (disease-specific survival) than those without POLE exonuclease domain mutations ( P =0.02). Determination of the POLE mutation status is important for the management of these patients.